2002
DOI: 10.1021/jf010767q
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Denaturation of Myofibrillar Proteins of Striated and Smooth Adductor Muscles of Scallop (Zygochlamyspatagonica). A Differential Scanning Calorimetric Study

Abstract: Denaturation of proteins from striated and smooth muscles of scallop (Zygochlamys patagonica) was studied with differential scanning calorimetry (DSC) by monitoring maximum temperatures of transition and denaturation enthalpies. DSC thermograms of both striated and smooth whole muscles showed two transitions: Tmax 55.0, 79.2 degrees C; and Tmax 54.7, 78.7 degrees C, respectively. The DSC thermograms of myofibrils and actomyosin were similar to those corresponding to their respective whole muscles. As pH and io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…ΔH signifi cantly decreased when ionic strength increased from 0.05 to 0.5 in both types of muscle. Striated muscles were affected more than smooth muscles by changes in the chemical environment (Paredi et al 2002). Three major endothermic peaks at 50, 57 and 74 °C were found in the DSC curve of the mantle of cuttlefi sh (Sepia esculenta).…”
Section: Dsc Measurements Taken On Invertebratesmentioning
confidence: 99%
“…ΔH signifi cantly decreased when ionic strength increased from 0.05 to 0.5 in both types of muscle. Striated muscles were affected more than smooth muscles by changes in the chemical environment (Paredi et al 2002). Three major endothermic peaks at 50, 57 and 74 °C were found in the DSC curve of the mantle of cuttlefi sh (Sepia esculenta).…”
Section: Dsc Measurements Taken On Invertebratesmentioning
confidence: 99%
“…In this way, the lower superficial hydrophobicity of Aulacomya actomyosin could be due to a greater stability of this protein before the chemical environment. Differential scanning calorimetric (DSC) studies demonstrated that the myosin-paramyosin zone of the thermogram for Aulacomya has great thermal stability than those obtained in DSC thermograms of squid and scallop muscles (Paredi, Tomas, Crupkin, & An˜on, 1998b;Paredi, Tomas, & Crupkin, 2002). In addition, a great sensitivity of Patagonian scallop myofibrillar proteins to changes in the chemical environment was reported Paredi, Tomas, & Crupkin, 2003).…”
Section: Enzymatic Activity and Protein Surface Hydrophobicitymentioning
confidence: 99%
“…DSC was widely used to analyze the proteins of muscle tissue from chicken, beef, pork and fish meat [11,12]. The DSC studies characterizing the thermal properties of muscle proteins in squid (Illex argentinus) [13] or scallop (Zygochlamys patagonica) [14] were reported. However, little DSC research has been done on muscle proteins from other marine or freshwater sources.…”
Section: Introductionmentioning
confidence: 99%